TO THE QUESTIONS OF INNOVATIVE APPROACH TO THE PROCESS OF PHYSICAL EDUCATION IN UNIVERSITY (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2022)
The article analyzes innovative methods of teaching physical culture at the university. Most students do not see interest in the subject "physical culture". Therefore, it becomes relevant for university teachers to introduce new methods and technologies for conducting classes in order to interest students. The paper considers the relevance and role of the search for new methods and technologies of teaching physical education, as well as the importance of the motivational mechanism. Examples of health-saving, personality-oriented, information and communication technologies are given.